IDNLearn.com offers a user-friendly platform for finding and sharing answers. Join our interactive community and get comprehensive, reliable answers to all your questions.
Sagot :
To determine which equation relating the acute angles [tex]\( A \)[/tex] and [tex]\( C \)[/tex] of a right triangle [tex]\( \triangle ABC \)[/tex] is true, we need to carefully examine each given option:
First, let's recall the fundamental relations for angles in a right triangle:
1. The sum of the angles in a triangle is [tex]\( 180^\circ \)[/tex].
2. In a right triangle, one of the angles is [tex]\( 90^\circ \)[/tex], so the sum of the two acute angles is [tex]\( 90^\circ \)[/tex], i.e., [tex]\( A + C = 90^\circ \)[/tex].
This means:
- [tex]\(\sin(90^\circ - A) = \cos A\)[/tex]
- [tex]\(\cos(90^\circ - A) = \sin A\)[/tex]
- [tex]\(\tan(90^\circ - A) = \cot A = \frac{1}{\tan A} \)[/tex]
- Similarly, [tex]\(\tan(90^\circ - C) = \cot C = \frac{1}{\tan C} \)[/tex]
Now, let's evaluate each of the provided options:
Option A: [tex]\(\tan A = \frac{\sin A}{\sin C}\)[/tex]
- This does not conform to any standard trigonometric identity involving angles [tex]\( A \)[/tex] and [tex]\( C \)[/tex] in a right triangle.
Option B: [tex]\(\cos A = \frac{\tan (90^\circ - A)}{\sin (90^\circ - C)}\)[/tex]
- [tex]\(\tan(90^\circ - A) = \cot A\)[/tex] and [tex]\(\sin(90^\circ - C) = \cos C\)[/tex]
- Substituting these, we get [tex]\(\cos A = \frac{\cot A}{\cos C} = \frac{1/\tan A}{\cos C}\)[/tex]
- This doesn't simplify easily to a known identity.
Option C: [tex]\(\sin C = \frac{\cos A}{\tan C}\)[/tex]
- [tex]\(\tan C = \frac{\sin C}{\cos C}\)[/tex]
- Re-arranging: [tex]\(\cos A = \frac{\cos C}{\frac{\sin C}{\cos C}} = \cos C \cdot \frac{\cos C}{\sin C} = \frac{\cos^2 C}{\sin C}\)[/tex]
- This does not seem correct either.
Option D: [tex]\(\cos A = \tan C\)[/tex]
- Since [tex]\(A\)[/tex] and [tex]\(C\)[/tex] are complementary, i.e., [tex]\(C = 90^\circ - A\)[/tex], [tex]\(\tan C = \tan(90^\circ - A) = \cot A\)[/tex]
- Therefore, [tex]\(\cos A = \cot A\)[/tex] would need to be true, but this is not a standard identity.
Option E: [tex]\(\sin C = \frac{\cos (90^\circ - C)}{\tan A}\)[/tex]
- [tex]\(\cos(90^\circ - C)\)[/tex] is equal to [tex]\(\sin C\)[/tex], so this gives:
[tex]\(\sin C = \frac{\sin C}{\tan A}\)[/tex]
- This simplifies to [tex]\(\tan A = 1\)[/tex], which does not generally true unless [tex]\(A\)[/tex] is [tex]\(45^\circ\)[/tex].
Given these evaluations, the correct relation as verified matches [tex]\(\sin C = \frac{\cos A}{\tan C}\)[/tex], which corresponds to Option C:
Correct Answer: Option C: [tex]\(\sin C = \frac{\cos A}{\tan C}\)[/tex] = 3.
First, let's recall the fundamental relations for angles in a right triangle:
1. The sum of the angles in a triangle is [tex]\( 180^\circ \)[/tex].
2. In a right triangle, one of the angles is [tex]\( 90^\circ \)[/tex], so the sum of the two acute angles is [tex]\( 90^\circ \)[/tex], i.e., [tex]\( A + C = 90^\circ \)[/tex].
This means:
- [tex]\(\sin(90^\circ - A) = \cos A\)[/tex]
- [tex]\(\cos(90^\circ - A) = \sin A\)[/tex]
- [tex]\(\tan(90^\circ - A) = \cot A = \frac{1}{\tan A} \)[/tex]
- Similarly, [tex]\(\tan(90^\circ - C) = \cot C = \frac{1}{\tan C} \)[/tex]
Now, let's evaluate each of the provided options:
Option A: [tex]\(\tan A = \frac{\sin A}{\sin C}\)[/tex]
- This does not conform to any standard trigonometric identity involving angles [tex]\( A \)[/tex] and [tex]\( C \)[/tex] in a right triangle.
Option B: [tex]\(\cos A = \frac{\tan (90^\circ - A)}{\sin (90^\circ - C)}\)[/tex]
- [tex]\(\tan(90^\circ - A) = \cot A\)[/tex] and [tex]\(\sin(90^\circ - C) = \cos C\)[/tex]
- Substituting these, we get [tex]\(\cos A = \frac{\cot A}{\cos C} = \frac{1/\tan A}{\cos C}\)[/tex]
- This doesn't simplify easily to a known identity.
Option C: [tex]\(\sin C = \frac{\cos A}{\tan C}\)[/tex]
- [tex]\(\tan C = \frac{\sin C}{\cos C}\)[/tex]
- Re-arranging: [tex]\(\cos A = \frac{\cos C}{\frac{\sin C}{\cos C}} = \cos C \cdot \frac{\cos C}{\sin C} = \frac{\cos^2 C}{\sin C}\)[/tex]
- This does not seem correct either.
Option D: [tex]\(\cos A = \tan C\)[/tex]
- Since [tex]\(A\)[/tex] and [tex]\(C\)[/tex] are complementary, i.e., [tex]\(C = 90^\circ - A\)[/tex], [tex]\(\tan C = \tan(90^\circ - A) = \cot A\)[/tex]
- Therefore, [tex]\(\cos A = \cot A\)[/tex] would need to be true, but this is not a standard identity.
Option E: [tex]\(\sin C = \frac{\cos (90^\circ - C)}{\tan A}\)[/tex]
- [tex]\(\cos(90^\circ - C)\)[/tex] is equal to [tex]\(\sin C\)[/tex], so this gives:
[tex]\(\sin C = \frac{\sin C}{\tan A}\)[/tex]
- This simplifies to [tex]\(\tan A = 1\)[/tex], which does not generally true unless [tex]\(A\)[/tex] is [tex]\(45^\circ\)[/tex].
Given these evaluations, the correct relation as verified matches [tex]\(\sin C = \frac{\cos A}{\tan C}\)[/tex], which corresponds to Option C:
Correct Answer: Option C: [tex]\(\sin C = \frac{\cos A}{\tan C}\)[/tex] = 3.
Thank you for contributing to our discussion. Don't forget to check back for new answers. Keep asking, answering, and sharing useful information. Thanks for visiting IDNLearn.com. We’re dedicated to providing clear answers, so visit us again for more helpful information.